Dowód prima facie w postępowaniu cywilnym dotyczącym szkód powstałych w związku z leczeniem - Białkowski, Michał (Naczelna Rada Adwokacka w Warszawie, 2014)
The objective of this paper is to present main perspectives expressed by representatives of Polish legal doctrine as well as several examples of applications of prima facie evidence in legal cases submitted to Polish Supreme Court. Although not codified in Polish civil procedure prima facie evidence is applied in cases concerning claims for compensation for damages such as those occurred during medical treatment or inflicted by employees. The paper tries to answer whether prima facie evidence is needed during judicial proceedings or if legal means presented to parties of litigation by Polish legislation are sufficient enough to assert their rights.
Keywords: dowód prima facie; błąd medyczny; roszczenie odszkodowawcze